Dance in Ancient Mesopotamia - Collon, Dominique (Near Eastern archaeology, 2003)
Dance depictions from the "heartland of cities" hold a particular fascination for those who are interested in this subject. Prehistoric pottery from Mesopotamia is known for its dynamic images of swirling dancers. Many of the dance positions shown on ancient ceramics and cylinder seals are echoed by the ceremonial dances of today's Iraqi tribespeople. From ancient motif to modern ethnography, the author, who is a well-known authority on Mesopotamian symbolism, traces the evolution of the dance from early farming cultures to modern times.